Traveller's Palm Tree, Botanic Garden, St. Anns, Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
This postcard shows a man standing next to some Traveller's Palms which often grow over 20 ft high and produces distinctive fan like leaves. The postcard is addressed to J. Gluck of London, England.
Colour: Sepia (print); Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Traveller's Palm; Ravenala madagascariensis; Botanical gardens; Plants